El desarrollo financiero como medida de reducción de la informalidad en países en vías de desarrollo (2007-2017) - Pizarro Moreno, Krisia (2019)
The present study proposes financial development as a mechanism for the reduction of informality in developing countries. It shows theoretical and empirical evidence of the negative relationship between the two issues, taking a sample of 29 upper middle-income countries for the period 2007-2017. Likewise, in order to test the hypotheses, an econometric model of panel data with random effects is applied, with which it is possible to conclude that, using the broad money as a measurement variable of financial development, the latter negatively impacts informality achieving economic growth for the countries in the sample in the long term. For this reason, it is recommended that the authorities of developing countries encourage financial inclusion in their economies through the creation of new financial instruments or the strengthening of existing ones, the reduction of credit restrictions and/or the articulation of government institutions. However, this drive to the financial sector will achieve a considerable reduction in informality only if it is accompanied by institutional changes and public expenditure reforms.